Correlation of Knowledge Level of Drugs (Doping) with Achievement Central Java Paragliding Athletes - Amin, Nur (Journal of Physical Education Health and Sport, 2022)
In facing the championship PON, athletes are required to have good stamina. However, with the pandemic that resulted in restrictions on activities, athletes were unable to prepare properly. Athletes whom found to have used the drug will be disqualified from the PON championship. The aim of this study was to determine the relationship between the level of knowledge of illegal drugs (doping) with the achievement of paragliding athletes in Central Java. The type of research used in this study is cross-sectional. Using the total sampling technique, the subjects obtained were 12 athletes who took part in the 20th PON Papua paragliding championship. The instruments used include a knowledge level questionnaire and a report on the results of the 20th PON Papua championship. The data obtained from the level of knowledge of illegal drugs was correlated with data obtained from the 20th PON Papua championship (achievement) report, then the data were analyzed by correlation test using the SPSS 23 application for windows. The results showed a significant relationship between the level of knowledge of illegal drugs (p=0,001), age (p=0,01) and licence (p=0,02) with the achievement of paragliding athletes in Central Java (R=87,3%). It can be concluded that the level of knowledge of illegal drugs (doping), age, and licence are a factor that can affect the performance of paragliding athletes in Central Java.